Integrating Halalan Thayyiban Principles in Herbal and Cosmetic Regulation: A Model for Religious and Scientific Convergence - Rahman, Najib Aulia (Sinergi International Journal of Islamic Studies, 2025)
The convergence between religious compliance and scientific safety protocols has become increasingly important in developing halal-certified cosmetics. This study investigates the integration of Halalan Thayyiban principles rooted in Islamic law and modern regulatory standards within Indonesia’s herbal and cosmetic industries. The objective is to develop a regulatory-scientific model that aligns the requirements of halal certification (HAS 23000, UU 33/2014) with quality assurance protocols (ISO 22716, PerBPOM 16/2024). Using a normative-qualitative approach, the study analyzes regulatory documents, certification procedures, and safety test standards. Key elements of the halal certification process are examined, including the SIHALAL platform, halal-critical ingredient mapping, and the documentation framework. Parallel to this, thayyib criteria are addressed through microbiological and chemical safety evaluations, product stability assessments, and patch testing protocols aligned with international benchmarks. Findings reveal strong compatibility between halal and thayyib systems, enabling the development of an integrated compliance model. The proposed framework incorporates regulatory checkpoints, supplier documentation, GMP alignment, and technological innovations such as RFID and blockchain for traceability. The study also identifies institutional roles, implementation challenges particularly among SMEs and strategic support mechanisms to enhance certification readiness. The integrated Halalan Thayyiban framework offers a dual benefit: it ensures syariah compliance while upholding modern safety standards, thus improving consumer trust and market positioning. These findings contribute to the discourse on regulatory harmonization and provide practical guidance for producers, auditors, and policymakers.